Proses berpikir konseptual siswa SMP ditinjau dari perbedaan kecemasan matematis - Bela, Sintya; Marlina, Rina (IKIP Siliwangi, 2024)
This study aims to analyze how the conceptual thinking process of seventh-grade junior high school students in solving social arithmetic problems when viewed from mathematical anxiety differences. The type of research was qualitative descriptive which used purposive sampling. There were 34 students of seventh-grade junior high school in West Karawang as the subject of this study. The data was collected through questionnaires about mathematical anxiety, written tests of conceptual thinking processes, interviews, and documentation. The data was analyzed by reducing data, presenting data, and drawing conclusions. The results of this study indicated that The result of this study showed that the majority of grade VII SMP students' mathematical anxiety tended to be moderate. The results of the analysis concluded that students with low mathematical anxiety had good conceptual thinking skills because they were able to fulfill all indicators. However, students with moderate mathematical anxiety had fairly good conceptual thinking skills because there was only one indicator that was not fulfilled, namely correcting answers. Furthermore, students with high mathematical anxiety had poor conceptual thinking skills since they were only able to fulfill two indicators, namely writing down the information they knew and recounting the steps they took.